Intratumoral heterogeneity of MYC drives medulloblastoma metastasis and angiogenesis. Issue 9 (21st March 2022) - Qin, Nan; Paisana, Eunice; Langini, Maike; Picard, Daniel; Malzkorn, Bastian; Custódia, Carlos; Cascão, Rita; Meyer, Frauke-Dorothee; Blümel, Lena; Göbbels, Sarah; Taban, Kübra; Bartl, Jasmin; et al.
Abstract: Background: Intratumoral heterogeneity is crucially involved in metastasis, resistance to therapy, and cancer relapse. Amplifications of the proto-oncogene MYC display notable heterogeneity at the single-cell level and are associated with a particularly dismal prognosis in high-risk medulloblastomas (MBs). The aim of this study was to establish the relevance of interclonal cross-talk between MYC-driven and non-MYC-driven MB cells. Methods: We used fluorescence in situ hybridization, single-cell transcriptomics, and immunohistochemistry, in vitro isogenic cell models, non-targeted proteomics, mass spectrometry-based metabolite quantification, HUVECs tube formation assay, and orthotopic in vivo experiments to investigate interclonal cross-talk in MB. Results: We found that the release of lactate dehydrogenase A (LDHA) from MYC-driven cells facilitates metastatic seeding and outgrowth, while secretion of dickkopf WNT signaling pathway inhibitor 3 from non-MYC-driven cells promotes tumor angiogenesis. This tumor-supporting interaction between both subclones was abrogated by targeting the secretome through pharmacological and genetic inhibition of LDHA, which significantly suppressed tumor cell migration. Conclusion: Our study reveals the functional relevance of clonal diversity and highlights the therapeutic potential of targeting the secretome to interrupt interclonal communication and progression in high-risk MB. Graphical Abstract: